The accidental countess eaudiobook Accidental (willingham) series, book 2. - Willingham, Michelle (Accidental, 2014)
RITA Award Finalist Michelle Willingham pens gripping romances that fans just can't put down. The Accidental Countess whisks listeners away to 19th-century England for a tale of passion and intrigue. Stephen Chesterfield, the Earl of Whitmore, cannot recall the past three months of his life-much less that he has a wife. And Emily Chesterfield finds herself trapped in a marriage of convenience to a man who doesn't even remember her. Now, as their romance rekindles, they much face issues of trust and loyalty even as a shadowy villain actively tries to keep the Earl's memories suppressed.